2015
DOI: 10.1093/inthealth/ihv026
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of injury problems among child labourers in a rural community of Bangladesh: findings from an injury surveillance system

Abstract: Working children are at risk of injury, death and illness in Bangladesh. Child labourers are now even more clearly tied to quantified morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…It is important to note, however, that the associations we describe are still evident when appropriate statistical controls are made for these between-group differences. Third, engagement in hazardous child labour may lead to an increased risk of acquiring a disability (Dalal et al, 2015;Forastieri, 1997;Ibrahim et al, 2019;Kuimi et al, 2018;Shendell et al, 2016;Sturrock & Hodes, 2016). It is not possible, at present, to compare the relative importance of these three general pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, however, that the associations we describe are still evident when appropriate statistical controls are made for these between-group differences. Third, engagement in hazardous child labour may lead to an increased risk of acquiring a disability (Dalal et al, 2015;Forastieri, 1997;Ibrahim et al, 2019;Kuimi et al, 2018;Shendell et al, 2016;Sturrock & Hodes, 2016). It is not possible, at present, to compare the relative importance of these three general pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are potential personal and social benefits to some forms of child work (Bourdillon & Carothers, 2019), evidence suggests that child labour is associated with poor growth and nutritional status; higher incidence of injuries, infectious and system-specific diseases, behavioural and emotional disorders; decreased coping efficacy; and lower educational attainment (Dalal, Rahman, Gifford, & Rahman, 2015;Ibrahim, Abdalla, Jafer, Abdelgadir, & de Vries, 2019;Kuimi, Oppong-Nkrumah, Kaufman, Nazif-Munoz, & Nandi, 2018;Shendell, Noomnual, Chishti, Allacci, & Madrigano, 2016;Sturrock & Hodes, 2016). Unsurprisingly, child labour under hazardous conditions is particularly detrimental to child health (Forastieri, 1997;International Labour Organization, 2018;Posso, 2019).…”
mentioning
confidence: 99%
“…The study shows their dissatisfaction in doing child labour in majority of the cases, which has a negative impact on the physiological and psychological levels of the children which have effects on mental health [26] [27]. Previous study from Bangladesh has indicated that child labourers are vulnerable to injuries, illness and death [12]. However, the current study has specifically indicated that child labour has different physical and mental health problems along with injuries.…”
Section: Discussionmentioning
confidence: 67%
“…The prevalence of mental disorders was noted to be as high as 20.1% compared with 12.5% in the general population [20]. Child labourers in Indian organized sectors are economically beneficial as they are 80% cheaper than members of the adult [12]. Economic and policies development is necessary to eliminate child labour [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation